Suburban Housing Development and Off-Grid Electric Power Supply Assessment for North-Central Nigeria - Ogundari, Ibikunle Olalekan; Akinwale, Yusuf Opeyemi; Adepoju, Adeyemi Oluseun; Atoyebi, Musiliyu Kunle; Akarakiri, Joshua Babatunde (International Journal of Sustainable Energy Planning and Management, 2017)
Energy infrastructures in North-Central Nigeria are inadequate and grid electricity is unable to meet suburban housing electricity demand. The alternative power-supply options proposed by government for the region require appropriation analysis for selection. Four public housing estates in suburban Abuja are selected for electricity demand analysis under conventional and energy-efficient lighting scenarios; then techno-economic parameters of two off-grid electric power supply systems (PV and Diesel-powered generation) to meet these electricity demands are evaluated. An energy techno-economic assessment methodology is used. The study determines the energy-efficient lighting system is appropriate with 40% energy savings relative to the Conventional Lighting Systems. The diesel generator alternative power-supply option has Life Cycle Costs almost 4 times those of the PV option. The study established the PV-energy-efficient lighting system as the most feasible off-grid electric power supply alternative for implementation.